2015
DOI: 10.14336/ad.2015.0620
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-1260b in Non-small Cell Lung Cancer is Associated with Lymph Node Metastasis

Abstract: Lymph node (LN) metastasis is often an early event in the progression of malignant tumors and it contributes to the majority of cancer mortalities. MiRNAs play key roles in tumor metastasis. This study aimed to investigate the specific miRNAs as putative indicators of metastasis early diagnosis for non-small cell lung cancer (NSCLC). In this study, five NSCLC cases with LN metastasis and four cases without metastasis (NLN) were enrolled for Agilent Human miRNA array. The interested differentially expressed miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…We observed an almost complete loss of miR-1260 from the Ago complexes in the four cell lines, in line with its association with Ago1 (41). This miRNA was shown to differentiate between GCB-and ABC-DLBCLs (42) and is considered to have oncogenic properties (43). We assume that the enrichment of growth-retarding miRNAs like miR-320a to a level only slightly above the 0.1% cutoff is offset by a rise of growth-promoting miRNAs, either by their overall level or by their Ago2 enrichment.…”
Section: Discussionsupporting
confidence: 66%
“…We observed an almost complete loss of miR-1260 from the Ago complexes in the four cell lines, in line with its association with Ago1 (41). This miRNA was shown to differentiate between GCB-and ABC-DLBCLs (42) and is considered to have oncogenic properties (43). We assume that the enrichment of growth-retarding miRNAs like miR-320a to a level only slightly above the 0.1% cutoff is offset by a rise of growth-promoting miRNAs, either by their overall level or by their Ago2 enrichment.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, we found that the expression of miR-23a-5p in RCC tissues is obviously higher than the expression in paired normal tissues. The result also happened on HCC and NSCLC (9,10). Meanwhile, upregulation of miR-23a-5p could promote the proliferation, migration and invasion in RCC cell lines while downregulation of miR-23a-5p played an inhibitory role in RCC cell lines.…”
Section: Discussionmentioning
confidence: 83%
“…miR-23a-5p was located at chromosome 19 and recently involved in various types of cancers, including hepatocellular carcinoma (9), non-small cell lung cancer (NSCLC) (10) and so on. But there is no study about miR-23a-5p in RCC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miRNA-1260b targets Wnt antagonist genes and inhibits tumor suppressor genes in renal cancer [37]. In addition, overexpression of miRNA-1260b has been reported to be involved in the metastasis of non-small cell lung cancer [38]. For miR-296-3p, it has exhibited resistance to natural killer cells to increase metastatic potential of prostate cancer cells [39].…”
Section: Discussionmentioning
confidence: 99%